Evaluation, operative management, and outcome after liver transplantation in children with biliary atresia and situs inversus. - Farmer, D G (1995)
INTRODUCTION: Biliary atresia, a common indication for liver transplantation, can be associated with situs inversus. Our experience with liver transplantation in children (n = 6) was reviewed retrospectively. PATIENTS AND METHODS: Preoperative duplex sonography, computerized tomography, and visceral angiography were obtained. Vascular anomalies identified included preduodenal portal vein (6/6), interrupted inferior vena cava (5/6), and aberrant hepatic artery (4/6). RESULTS: The liver graft was placed in a midline position. Venous continuity was achieved by donor suprahepatic inferior vena cava to recipient hepatic cloaca and direct end-to-end portal anastomosis. The donor infrahepatic inferior vena cava was oversewn. Arterial continuity was restored using either a direct branch-patch anastomosis (3/6) or a supraceliac aortic interposition graft (3/6). In retrospect, preoperative diagnostic work-up was noncontributory and outcome was not complicated by pre-existing situs inversus. CONCLUSION: Situs inversus in liver recipients requires operative technical modifications, but does not change outcome. Furthermore, extensive preoperative work-up should be avoided.